Constructtivism Mathematics Learning with Search, Solve, Create, and Share (SSCS) Model to Improve Mathematics Disposition and Student Concept Understanding of Limit Function Materials of XI Natural Science Class - Rakhmi, Delta Aringga; Kartono, Kartono; Mastur, Zaenuri (Unnes Journal of Mathematics Education Research, 2018)
The objectiveof this study is to determine the implementation of constructivism learning throughsearch, solve, create, and shareto improve concept comprehension ability in limit function of XI graderswhich is effective with a valid and practical instrument and refers to the modified Plomp model. The concept comprehension ability testdatawere processed by using t-test, proportion z, sample t-test, regression, and Gain test. The results of learning instrument development are as follows: (1) The averageof syllabus is 4.38, Lesson Plan 4.42, book 3,98, Students’ Worksheet 4.35, and concept comprehension ability test4,00; (2) this learning is effective, it is marked by achieving: a) the concept comprehension ability of experiment class fulfillsthe Minimum Mastery Criteria, b) the disposition and activeness respectively have a positive effect on KPK, c) KPK experimental class with an average of 81.24 better than control class is 71.18, d) Increasing the experiment test class by 59%. Based on the validation results, it is obtained by a valid instrument and test results, it is obtained effective learning, then the objective of the development of the instrument is achieved.